Estudo sobre desruptores endócrinos em sistemas aquáticos: detecção e perspectivas de tratamento das águas do Rio Aporé-MS/GO, utilizando-se adsorventes sólidos - Garcia, Edemir Feliciano [UNESP] (2014)
Endocrine disrupters chemical (EDC), such as pesticides, represent an emerging class of contaminants in aquatic systems that can compromise the life of aquatic biota and human. Although some studies are being developed to quantify and verify the toxicity of EDC in the environment, there is almost no literature records related to the conduct studies and availability of these substances in surface waters. The aim of this study was to verity the presence of herbicide 2,4-D (diclorfenoxacetic acid), Atrazine and Linuron and insecticide Methyl Paration in Aporé River to propose perspectives of treatment in these waters by using low cost adsorbents. This river is located at the Brazilian savanna region, river that is located between Mato Grosso do Sul state and Goias state and receives a great amount of agricultural production waste. After collecting an amount of water at strategic points, has been done an extraction by the technical of Solid Phase Extraction, in cartridges of silica C-18, the detection in Gas Chromatography, attached with a detector Mass Spectrometry. The materials tested for the removal of pesticides, targeted in this study, were obtained from the: i) organically modified clays with surfactant N-dodecyl-2-pyrrolidone (Mo-DDP); ii) PET- Polyethylene terephthalate bottle after use (PET); III) biomass of J. curcas L. (TPMAN); iv) rice husk ash (RHA); v) silica gel organically modified with 2-Amino-1,3,4-thiadiazole (SGT) and vi) activated carbon from coconut shell (AC). Studies of detection and quantification of pesticides on the Aporé River‘s water demonstrate the presence of pesticides Malathion and Dibutyl phthalate(DBP), which are considered EDC by Brazilian, American and European government agencies. The adsorbents used had positive parameters to use for removal of these molecules, both in batch studies when fixed bed. The adsorption parameters tested showed that 60 to 120 min. ...